Predicting Consumer Behavior Toward Healthy Beverages In Surabaya (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2023)
ABSTRACTThis study investigates consumer behavior toward healthy beverages and examines the impacts of subjective norms and attitudes toward healthy beverages on the purchase intention of healthy beverage products. In this study, consumers' long-term orientation, health concerns, and Trust in healthy beverage products influenced attitudes toward healthy beverages. It was conducted in Surabaya City, Indonesia, and the sample size consisted of 137 consumers of healthy drinks in Surabaya. Structural Equation Modeling was applied to measure the relationship among the constructs. The results indicated that health concerns and long-term orientation did not influence consumers' attitudes toward healthy beverages. Purchase intention was not affected by health concerns and long-term orientation through Attitude. However, Trust influenced consumers' attitudes toward healthy beverages, and Trust was proven to impact purchase intention with Attitude as the mediating factor. Attitude and subjective norm had a positive relationship toward purchase intention. Keywords: Healthy Beverages, Consumer Behavio, Trust; Attitude, Subjective Norm.